(untitled) (Gestión y Gerencia, 2023)
Public organizations start from planning and a systemic order where people, norms, values, processes, organization manuals and functions, decisions and other factors intervene to meet their objectives and goals; this order can be affected by the complexity of its operation that involves traditional, rigid, bureaucratic management schemes, lack of leadership and incentives that translate into motivation, little effective communication, inefficiency in decision-making processes and resistance to change, generating a natural tendency toward disorder and loss of effectiveness in the organizational system. Entropy is degradation, disorder, inefficiency or uncertainty in the functioning of a system. The purpose of the essay is to give an ontological and epistemological look at entropy in public organizations. As epistemic theoretical references, from entropy, it is based on the general systems theory of Bertalanffy (1968), the complexity theory of Morín (2006), and the contributions of Osborne and Gaebler (1992) on public organizations. The methodology used, after a documentary review of the theories and the dialogic exchange with directors of public organizations, was the phenomenology developed by Husserl (1949), supported by the hermeneutics of Gadamer (1960). Conclusion, if the traditional management approach places emphasis on the activities of the administrative process, such as planning, organizing, directing and controlling; from entropy, all non-controllable events, disorder, uncertainty and chaos are considered, which must also be considered from management, especially in public organizations.